Toward a Modern Synthesis of Immunity: Charles A. Janeway Jr. and the Immunologist’s Dirty Little Secret - Gayed, Peter M. (YJBM, 2011)
This essay chronicles the major theoretical and experimental contributions made by Charles A. Janeway, Jr. (1943-2003), Howard Hughes Medical Institute investigator and Yale Professor of Immunobiology, who established the fundamental role of the innate immune system in the induction of the adaptive arm.